P285 Associations between occupational exposure to outdoor air pollution and obstructive lung disease – register based data from the copenhagen airport cohort. (1st September 2016) - Brauer, Charlotte; Møller, KL; Mikkelsen, S; Loft, S; Bonde, JP; Ebbehøj, N; Simonsen, EB; Koblauch, H; Alkjær, T; Helweg-Larsen, K; Thygesen, LC
Abstract : Introduction: Outdoor air pollution is associated with exacerbations of obstructive lung diseases, but the role of air pollution in the incidence of these diseases is unclear. At Copenhagen Airport a high number of particles have been measured especially on the apron at the terminal gates where many persons work with ground handling services. Aims: To assess whether long-term occupational exposure to outdoor air pollution at an airport was associated with the incidence of obstructive lung disease. Methods: A cohort of 6, 629 male airport employees and a reference group of 62, 546 men was followed from 1990 to 2012 in the Danish National Patient Register that covers all contacts to hospitals. The primary exposure measure was cumulative years of work at the airport weighted with the proportion of time spent on the apron ('apron-years'). The outcome was a first time registration in the Patient Register of chronic obstructive pulmonary disease (COPD), asthma or all obstructive lung diseases together. Incidence rate ratios (IRR) were estimated from Poisson models adjusting for age, education, and calendar year. Results: The reference group had a higher incidence rate than the group of exposed airport employees of COPD (IRR = 1.50; 95% CI: 1.21–1.85) and all obstructive lung diseases (IRR = 1.20; 1.03–1.39), but the same incidence rate of asthma (0.99; 0.81–1.20). In analyses of the internal dose-response relationship among the airport employees, we found no association between cumulated 'apron-years' and incidence of COPD. Regarding asthma, airport employees with 7+ apron-years had lower incidence rate (IRR = 0.57; 0.34–0.95) than airport employees with 0.1–3 years 'apron-years'. However, we found no linear effect of cumulated 'apron-years' on asthma (IRR = 0.97; 0.94–1.01). Conclusions: This large register-based cohort study found no evidence of associations between cumulative occupational exposure to air pollution and incidence of obstructive lung disease.